The occurrence and molecular detection of mcr-1 and mcr-5 genes in Enterobacteriaceae isolated from poultry and poultry meats in Malaysia - Karim, Md Rezaul; Zakaria, Zunita; Hassan, Latiffah; Faiz, Nik Mohd; Ahmad, Nur Indah (Frontiers in Microbiology, 2023)
The advent of antimicrobials-resistant (AMR), including colistin-resistant bacteria, poses a significant challenge to animal and human health, food safety, socio-economic growth, and the global environment. This study aimed to ascertain the colistin resistance prevalence and molecular mechanisms of colistin resistance in Enterobacteriaceae. The colistin resistance was determined using broth microdilution assay, PCR; and Sanger sequencing of mcr genes responsible for colistin resistance in Enterobacteriaceae (n=627), including Escherichia. coli (436), Salmonella spp. (n=140), and Klebsiella pneumoniae (n=51), obtained from chicken and chicken meats. Out of 627 Enterobacteriaceae, 8.6% of isolates exhibited colistin resistance phenotypically. Among these colistin resistant isolates, 9.3% (n=37) were isolated from chicken meat, 7.2% (n=11) from the cloacal swab of chicken and 7.9% (n=6) from the litter samples. Overall, 12.96% of colistin-resistant isolates were positive with mcr genes, in which mcr-1 and mcr-5 genes were determined in 11.11% and 1.85% of colistin-resistant isolates, respectively. The mcr-1 was detected in E. coli isolates, and mcr-5 was detected in Salmonella spp. isolate. The E. coli isolates obtained from chicken meats, cloacal swabs and litter samples were found positive for mcr-1, and Salmonella spp. originated from the chicken meat sample was observed with mcr-5, whereas no mcr genes were observed in K. pneumoniae strains isolated from any of the collected samples. The other colistin resistance genes, including mcr-2, mcr-3, mcr-4, mcr-6, mcr-7, mcr-8, mcr-9, and mcr-10 were not detected in the studied samples. The mcr-1 and mcr-5 genes were sequenced and found to be 100% identical l compared to the respective mcr-1 and mcr-5 gene sequences available in the NCBI database. This is the first report of colistin resistance mcr-5 gene in Malaysia which could portend the emergence of mcr-5 harboring bacterial strains for infection and threaten the use of colistin as a last-line antibiotic. Further studies are needed to characterize the mr-5 harbouring bacteria for the determination of plasmid associated with mcr-5 gene.